PENGARUH PROMOSI, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN SHOPEEFOOD DI KOTA MEDAN - Sihombing, Frisilia Dewi Raphon; Mardhiyah , Ainun (Transpublika Publisher, 2023)
This study aims to determine how the effect of promotion, price and service quality on customer satisfaction partially and simultaneously on Shopeefood customers in Medan City. This study employs a quantitative technique with an associative approach. The participants in this study are Shopeefood consumers in Medan City. Purposive sampling was used using 100 respondents as the research sample. Primary data for this study came via distributing questionnaires using Google Forms, while secondary data came from books and publications linked to this topic. The validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing are all significant to customer satisfaction. According to the coefficient of determination test, the result of Adjusted R Square is 0,710, which suggests that the influence of promotion, pricing, and service quality can explain 71% of customer satisfaction, while the remaining 29% is influenced by additional variables not described in this study.